Potential for commercial PlanetScope satellites in oil response monitoring. (October 2022) - Schaeffer, Blake A.; Whitman, Peter; Conmy, Robyn; Salls, Wilson; Coffer, Megan; Graybill, David; Lebrasse, Marie C.
Abstract: Extraction of petroleum oil resources may result in oil spills in the aquatic environment. Active and passive satellites are generally limited in either spatial coverage, temporal revisit periods, or spatial resolution when tracking surface oil slicks. PlanetScope passive satellites are reported to have near daily global coverage at a resolution of 3.5 m at nadir. These satellites may complement monitoring and fill temporal gaps by leveraging sun glint caused by the nadir viewing angle. Here, we demonstrate potential for PlanetScope satellite usage by investigating overpass timing and sun glint intensity. The United States potential for use was greatest during summer solstice and at lower latitudes. When combined with other high-resolution active and passive satellites, PlanetScope coverage added an average of 86.3 days each year from January 2018 through December 2020, as demonstrated at the Mississippi Canyon Block 20 Saratoga Platform site in the Gulf of Mexico. Highlights: PlanetScope satellites may benefit from sun glint to monitor surface oil slicks. Glint opportunities were greatest at the summer solstice with low wind speed. Glint opportunities generally increased at lower latitudes and wind speeds. PlanetScope may fill temporal gaps between other missions at high spatial resolution.